KAJIAN SOSIAL EKONOMI DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI KELAPA SAWIT DI KABUPATEN TULANG BAWANG - Rahma Lalita; R Hanung Ismono; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to determine the social, economic and welfare level of oil palm farmer households in Tulang Bawang Regency. The study was conducted in August 2017. The research sample was 54 farmers who are divided into two categories, namely 46 farmers of narrow land and 8 farmers of wide land.  The data is analyzed by qualitative description.  The level of well-being is measured by socio-metric indicators.  The results of the study showed that the average farmer respondents in the study area either of narrow land or wide land had good social categories conditions. Income earned by farmers from oil palm farming of narrow land was Rp29,941,900 / year with a contribution of  83.87% and of labor was 3.91% from the available 329 men working day/year.  Farmers of the wide area had earned Rp86,165,100/year from oil palm farming with a contribution of 94.65% and of labor was 19.82% of the 329 men working day/year.  The level of welfare showed that both of  narrow land and large land were in the category of not poor.Key words: economic conditions, oil palm, social conditions, welfare